Self-adhesive PET (polyethylene terephthalate) adhesive tape with stable performance and preparation method of self-adhesive PET adhesive tape
By coating the composite antistatic fluid on the surface of the PET film layer and preparing enhanced self-adhesive glue, the stability problem of self-adhesive PET tape in electrostatic and high-temperature environments is solved, and better viscosity and high-temperature stability are achieved.
Patent Information
- Application Number
- CN202510273904.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Self-adhesive PET tape is prone to adsorbing static debris during use, resulting in reduced viscosity and aesthetics. It is poor in stability in high-temperature electrolyte environment, which is prone to problems of chemical decomposition and mechanical properties.
The PET film layer is coated with antistatic fluids composed of γ-aminopropyltriethoxysilane, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and sodium dodecyl sulfate to form a stable antistatic layer, and a reinforced self-adhesive glue is prepared using polyurethane acrylate, heptadecafluorodecyl triethoxysilane and modified polysaccharide nanoparticles to form a crosslinking network to improve stability.
The electrostatic reduction and viscosity improvement of PET tape is achieved, while maintaining the stability and bonding properties of the glue in a high-temperature electrolyte environment to avoid chemical decomposition and mechanical properties.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PET tapes, and in particular to a self-adhesive PET tape with stable performance and a preparation method thereof. Background Art
[0002] Self-adhesive PET tape is a tape made by coating high-performance pressure-sensitive adhesive on one or both sides of a PET substrate. It has the advantages of excellent bonding performance, stable physical and chemical properties, strong environmental weather resistance, and good insulation performance. It is widely used in the fields of electronics, packaging, and architectural decoration.
[0003] Since PET materials are prone to static electricity, dust, hair and other debris may be adsorbed during use, affecting the stickiness and aesthetics of the tape. Antistatic additives are generally added to reduce static electricity. However, due to the long molecular weight of PET molecules and strong mutual entanglement, it is difficult for antistatic agent molecules to enter between PET molecular segments, making it difficult to disperse, resulting in poor affinity between the antistatic agent and PET. It is difficult for the antistatic agent to spread and adsorb evenly on the PET surface, and it is easy to agglomerate or unevenly, resulting in unstable antistatic effect. At the same time, the glue of self-adhesive PET tape has poor stability in a high-temperature electrolyte environment, and is prone to chemical decomposition, reduced mechanical properties, and poor bonding properties.
[0004] Based on this, the present invention designs a self-adhesive PET tape with stable performance and a preparation method thereof to solve the above problems. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a self-adhesive PET tape with stable performance and a preparation method thereof.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A self-adhesive PET tape with stable performance, comprising a modified PET film layer, a reinforced self-adhesive glue coated on one side of the modified PET film layer, and an outer layer of removable release paper; The modified PET film layer includes a PET film base layer and an antistatic liquid coated on the surface thereof, wherein the antistatic liquid includes the following raw materials in parts by weight: 5.2 to 7.3 parts of γ-aminopropyltriethoxysilane, 6.6 to 10.4 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, and 1.3 to 2.8 parts of sodium dodecyl sulfate; The enhanced self-adhesive glue comprises the following raw materials in parts by weight: 55-80 parts of polyurethane acrylate, 5-12 parts of heptadecafluorodecyltriethoxysilane and 5-10 parts of modified polysaccharide nanoparticles, wherein the modified polysaccharide nanoparticles are prepared from dialdehyde chitosan, alginate and konjac glucomannan.
[0007] Furthermore, the preparation method of the antistatic liquid is as follows: a mixed solvent is prepared according to a volume ratio of ethanol: water = 4:1; under stirring conditions, γ-aminopropyltriethoxysilane is slowly added to the mixed solvent, and the dropping speed is about 1 to 3 drops per second; after the dropping is completed, the pH of the solution is adjusted to 5 to 6, and stirring is continued for 1 to 1.5 hours to fully hydrolyze the γ-aminopropyltriethoxysilane to obtain a hydrolyzate; dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and sodium dodecyl sulfate are added to the hydrolyzate, and stirring is continued for 15 to 25 minutes to obtain an antistatic liquid.
[0008] Furthermore, the preparation method of dialdehyde chitosan is as follows: dissolve 3g of chitosan in 100mL of 0.3mol / L sodium periodate solution, stir for 3h in a dark place to fully oxidize the chitosan; then add 10mL of 0.1mol / L ethylene glycol solution to terminate the reaction; put the product into a dialysis bag and dialyze for 2 days; finally, freeze-dry the dialysate to obtain dialdehyde chitosan.
[0009] Furthermore, the preparation method of the modified polysaccharide nanoparticles is: Step (1), preparing a dialdehyde chitosan solution; Step (2), preparing a konjac glucomannan solution; Step (3), adding alginate to the dialdehyde chitosan solution, magnetically stirring for 15 to 25 minutes, to prepare an alginate-dialdehyde chitosan solution precursor; then mixing the alginate-dialdehyde chitosan solution precursor with the konjac glucomannan solution, ultrasonically treating, and then adjusting the pH of the solution to neutral; then stirring and incubating the neutral mixed solution at 25 to 32° C. for 1 to 2 hours, with a stirring speed of 350 to 550 r / min; then centrifuging to separate nanoparticles, and then, after washing and drying, freezing the modified polysaccharide nanoparticles at -40 to -70° C. for 1 to 3 hours, and storing at room temperature.
[0010] Furthermore, in step (1), dialdehyde chitosan is dissolved in 1-1.2% acetic acid solution to obtain a dialdehyde chitosan solution.
[0011] Furthermore, in step (2), konjac glucomannan is dissolved in water having a volume 3 to 5 times that of konjac glucomannan to obtain a konjac glucomannan solution.
[0012] Furthermore, the ultrasonic treatment power is 1200 W, and the ultrasonic treatment time is 5 to 12 minutes.
[0013] Furthermore, the preparation method of the enhanced self-adhesive glue is: polyurethane acrylate, heptadecafluorodecyl triethoxysilane and modified polysaccharide nanoparticles are mixed at 55-65° C. and then allowed to stand for at least 10 hours to obtain the enhanced self-adhesive glue.
[0014] In order to better achieve the purpose of the present invention, the present invention also provides a method for preparing a self-adhesive PET tape with stable performance, comprising the following steps: Step 1: Prepare a modified PET film layer. The specific steps are as follows: Step 1.1, prepare antistatic liquid: Prepare a mixed solvent according to the volume ratio of ethanol: water = 4:1; slowly add γ-aminopropyltriethoxysilane to the mixed solvent under stirring, with a drop rate of about 1 to 3 drops per second; after the drop addition is completed, adjust the pH of the solution to 5 to 6, continue stirring for 1 to 1.5 hours, so that the γ-aminopropyltriethoxysilane is fully hydrolyzed to obtain a hydrolyzate; add dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and sodium dodecyl sulfate to the hydrolyzate, continue stirring for 15 to 25 minutes, and obtain an antistatic liquid; Step 1.2, coating the surface of the PET film base with an antistatic liquid, and drying at a low temperature of 55° C. to obtain a modified PET film layer; Step 2: Apply enhanced self-adhesive glue on one side of the modified PET film layer. The specific steps are as follows: Step 2.1, preparing modified polysaccharide nanoparticles: adding alginate to a dialdehyde chitosan solution to prepare an alginate-dialdehyde chitosan solution precursor; then mixing the alginate-dialdehyde chitosan solution precursor with a konjac glucomannan solution, ultrasonically treating, and then adjusting the pH of the solution to neutral; then stirring and incubating the neutral mixed solution at 25-32°C for 1-2h, with a stirring speed of 350-550r / min; then centrifuging and separating the nanoparticles, and then freezing the modified polysaccharide nanoparticles at -40--70°C for 1-3h after washing and drying, and storing at room temperature; Step 2.2, blending polyurethane acrylate, heptadecafluorodecyl triethoxysilane and modified polysaccharide nanoparticles at 55-65° C. and standing for at least 10 hours to obtain an enhanced self-adhesive glue, coating the enhanced self-adhesive glue on one side of the modified PET film layer and drying; Step 3: Paste the removable release paper on the outside of the enhanced self-adhesive glue to obtain a self-adhesive PET tape with stable performance.
[0015] In order to better achieve the purpose of the present invention, the present invention also provides a self-adhesive PET tape with stable performance prepared according to the method.
[0016] Compared with the prior art, the present invention has the following beneficial effects: the present invention forms a stable antistatic system by compounding γ-aminopropyltriethoxysilane (KH-550), dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and sodium dodecyl sulfate (SDS), forms an antistatic layer on the surface of a PET film base layer by coating, and the silanol groups generated by the hydrolysis of KH-550 can undergo a condensation reaction with the hydroxyl groups on the surface of the PET film base layer to form a covalent bond, so that the silane is firmly attached to the surface of the PET film base layer; when a certain hydrolysis reaction occurs, the dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride can also react with the silanol groups generated by the hydrolysis of KH-550, so as to further enhance the adhesion stability of the antistatic system on the surface of the PET film base layer, and SDS is conducive to achieving uniform spreading of the antistatic system on the surface of the PET film base layer.
[0017] The present invention uses polyurethane acrylate, heptadecafluorodecyl triethoxysilane and modified polysaccharide nanoparticles to prepare enhanced self-adhesive glue. The aldehyde group in the dialdehyde chitosan molecule can react with the carboxyl group and hydroxyl group in the alginate molecule and the hydroxyl group in the konjac glucomannan molecule, thereby forming a cross-linked network between the three polymers, which is conducive to the later formation of a film with certain barrier properties, enhances resistance to chemical components, and avoids severe deformation or decomposition at high temperatures. Finally, the enhanced self-adhesive glue is highly stable in a high-temperature electrolyte environment. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Embodiment 1: In some embodiments, a method for preparing a self-adhesive PET tape with stable performance comprises the following steps: 1. Prepare the modified PET film layer. The specific steps are as follows: 1.1. Preparation of antistatic liquid: Weigh the following raw materials by weight: 5.2 parts of γ-aminopropyltriethoxysilane (KH-550), 10.4 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, and 1.3 parts of sodium dodecyl sulfate (SDS); A mixed solvent was prepared in a ratio of ethanol to water = 4:1 (v / v); under stirring (200 r / min), γ-aminopropyltriethoxysilane was slowly added dropwise to the mixed solvent at a rate of about 3 drops per second; after the addition was completed, the pH of the solution was adjusted to 5, and stirring was continued for 1.5 h to fully hydrolyze the γ-aminopropyltriethoxysilane to obtain a hydrolyzate; dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and sodium dodecyl sulfate were added to the hydrolyzate, and stirring was continued for 15 min to obtain an antistatic liquid.
[0020] 1.2. Coat the antistatic liquid on the surface of the PET film base (except the side coated with the enhanced self-adhesive glue), and dry it at a low temperature of 55°C to obtain a modified PET film layer; 2. Apply enhanced self-adhesive glue on one side of the modified PET film layer. The specific steps are as follows: 2.1. Preparation of dialdehyde chitosan: 3 g chitosan was dissolved in 100 mL 0.3 mol / L sodium periodate solution, stirred for 3 h in dark place to fully oxidize the chitosan; then 10 mL 0.1 mol / L ethylene glycol solution was added to terminate the reaction; the product was placed in a dialysis bag and dialyzed for 2 days; finally, the dialysate was freeze-dried to obtain dialdehyde chitosan (DCS); 2.2. Preparation of modified polysaccharide nanoparticles: (1) dissolving 5 parts of dialdehyde chitosan in 1% (v / v) acetic acid solution to obtain a dialdehyde chitosan solution; (2) dissolving 3.8 parts of konjac glucomannan in water having a volume 5 times that of the konjac glucomannan to obtain a konjac glucomannan solution; (3) 2.6 parts of alginate were added to the dialdehyde chitosan solution and magnetically stirred for 15 minutes to prepare an alginate-dialdehyde chitosan solution precursor; the alginate-dialdehyde chitosan solution precursor was then mixed with the konjac glucomannan solution and treated with ultrasound (power 1200 W) for 12 minutes, and then the pH of the solution was adjusted to neutral; the neutral mixture was stirred and incubated at 25°C for 2 hours at a stirring speed of 350 r / min; the nanoparticles were then separated by centrifugation, and after washing and drying, the modified polysaccharide nanoparticles were frozen at -70°C for 1 hour and stored at room temperature.
[0021] 2.3. Weigh the raw materials according to weight: 55 parts of polyurethane acrylate, 12 parts of heptadecafluorodecyltriethoxysilane and 5 parts of modified polysaccharide nanoparticles.
[0022] 2.4. Blend polyurethane acrylate, heptadecafluorodecyl triethoxysilane and modified polysaccharide nanoparticles at 55° C. and let stand for 10 hours to obtain enhanced self-adhesive glue. Coat the enhanced self-adhesive glue on one side of the modified PET film layer and dry it.
[0023] 3. Paste the removable release paper on the outside of the enhanced self-adhesive glue to obtain a self-adhesive PET tape with stable performance.
[0024] Embodiment 2: In some embodiments, a method for preparing a self-adhesive PET tape with stable performance comprises the following steps: 1. Prepare the modified PET film layer. The specific steps are as follows: 1.1. Preparation of antistatic liquid: Weigh the following raw materials by weight: 7.3 parts of γ-aminopropyltriethoxysilane (KH-550), 6.6 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, and 2.8 parts of sodium dodecyl sulfate (SDS); A mixed solvent was prepared in a ratio of ethanol to water = 4:1 (v / v); under stirring (300 r / min), γ-aminopropyltriethoxysilane was slowly added dropwise to the mixed solvent at a dropping speed of about 1 drop per second; after the addition was completed, the pH of the solution was adjusted to 6, and stirring was continued for 1 hour to fully hydrolyze the γ-aminopropyltriethoxysilane to obtain a hydrolyzate; dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and sodium dodecyl sulfate were added to the hydrolyzate, and stirring was continued for 25 minutes to obtain an antistatic liquid.
[0025] 1.2. Coat the antistatic liquid on the surface of the PET film base (except the side coated with the enhanced self-adhesive glue), and dry it at a low temperature of 55°C to obtain a modified PET film layer; 2. Apply enhanced self-adhesive glue on one side of the modified PET film layer. The specific steps are as follows: 2.1. Preparation of dialdehyde chitosan: 3 g chitosan was dissolved in 100 mL 0.3 mol / L sodium periodate solution, stirred for 3 h in dark place to fully oxidize the chitosan; then 10 mL 0.1 mol / L ethylene glycol solution was added to terminate the reaction; the product was placed in a dialysis bag and dialyzed for 2 days; finally, the dialysate was freeze-dried to obtain dialdehyde chitosan (DCS); 2.2. Preparation of modified polysaccharide nanoparticles: (1) dissolving 5 parts of dialdehyde chitosan in 1.2% (v / v) acetic acid solution to obtain a dialdehyde chitosan solution; (2) dissolving 3.2 parts of konjac glucomannan in water having a volume three times that of the konjac glucomannan to obtain a konjac glucomannan solution; (3) 2.4 parts of alginate were added to the dialdehyde chitosan solution and magnetically stirred for 25 minutes to prepare an alginate-dialdehyde chitosan solution precursor; the alginate-dialdehyde chitosan solution precursor was then mixed with the konjac glucomannan solution and treated with ultrasound (power 1200 W) for 5 minutes, and then the pH of the solution was adjusted to neutral; the neutral mixture was stirred and incubated at 32°C for 1 hour at a stirring speed of 550 r / min; the nanoparticles were then separated by centrifugation, and after washing and drying, the modified polysaccharide nanoparticles were frozen at -40°C for 3 hours and stored at room temperature.
[0026] 2.3. Weigh the raw materials according to weight: 80 parts of polyurethane acrylate, 5 parts of heptadecafluorodecyltriethoxysilane and 10 parts of modified polysaccharide nanoparticles.
[0027] 2.4. Blend polyurethane acrylate, heptadecafluorodecyl triethoxysilane and modified polysaccharide nanoparticles at 65° C. and let stand for 11 hours to obtain enhanced self-adhesive glue. Coat the enhanced self-adhesive glue on one side of the modified PET film layer and dry it.
[0028] 3. Paste the removable release paper on the outside of the enhanced self-adhesive glue to obtain a self-adhesive PET tape with stable performance.
[0029] Embodiment 3: In some embodiments, a method for preparing a self-adhesive PET tape with stable performance comprises the following steps: 1. Prepare the modified PET film layer. The specific steps are as follows: 1.1. Preparation of antistatic liquid: Weigh the following raw materials by weight: 6.5 parts of γ-aminopropyltriethoxysilane (KH-550), 8.4 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, and 2.4 parts of sodium dodecyl sulfate (SDS); A mixed solvent was prepared in a ratio of ethanol to water = 4:1 (v / v); under stirring (250 r / min), γ-aminopropyltriethoxysilane was slowly added dropwise to the mixed solvent at a dropping speed of about 2 drops per second; after the addition was completed, the pH of the solution was adjusted to 5.5, and stirring was continued for 1.2 h to fully hydrolyze the γ-aminopropyltriethoxysilane to obtain a hydrolyzate; dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and sodium dodecyl sulfate were added to the hydrolyzate, and stirring was continued for 20 min to obtain an antistatic liquid.
[0030] 1.2. Coat the antistatic liquid on the surface of the PET film base (except the side coated with the enhanced self-adhesive glue), and dry it at a low temperature of 55°C to obtain a modified PET film layer; 2. Apply enhanced self-adhesive glue on one side of the modified PET film layer. The specific steps are as follows: 2.1. Preparation of dialdehyde chitosan: 3 g chitosan was dissolved in 100 mL 0.3 mol / L sodium periodate solution, stirred for 3 h in dark place to fully oxidize the chitosan; then 10 mL 0.1 mol / L ethylene glycol solution was added to terminate the reaction; the product was placed in a dialysis bag and dialyzed for 2 days; finally, the dialysate was freeze-dried to obtain dialdehyde chitosan (DCS); 2.2. Preparation of modified polysaccharide nanoparticles: (1) dissolving 5.5 parts of dialdehyde chitosan in 1.1% (v / v) acetic acid solution to obtain a dialdehyde chitosan solution; (2) dissolving 3.4 parts of konjac glucomannan in water having a volume 4 times that of the konjac glucomannan to obtain a konjac glucomannan solution; (3) 2.1 parts of alginate were added to the dialdehyde chitosan solution and magnetically stirred for 20 minutes to prepare an alginate-dialdehyde chitosan solution precursor; the alginate-dialdehyde chitosan solution precursor was then mixed with the konjac glucomannan solution and treated with ultrasound (power 1200 W) for 10 minutes, and then the pH of the solution was adjusted to neutral; the neutral mixture was stirred and incubated at 28°C for 1.3 hours at a stirring speed of 400 r / min; the nanoparticles were then separated by centrifugation, and after washing and drying, the modified polysaccharide nanoparticles were frozen at -55°C for 2 hours and stored at room temperature.
[0031] 2.3. Weigh the following raw materials by weight: 69 parts of polyurethane acrylate, 7.4 parts of heptadecafluorodecyltriethoxysilane and 8.6 parts of modified polysaccharide nanoparticles.
[0032] 2.4. Polyurethane acrylate, heptadecafluorodecyl triethoxysilane and modified polysaccharide nanoparticles are mixed at 58° C. and allowed to stand for 10 hours to obtain a reinforced self-adhesive glue. The reinforced self-adhesive glue is coated on one side of the modified PET film layer and dried.
[0033] 3. Paste the removable release paper on the outside of the enhanced self-adhesive glue to obtain a self-adhesive PET tape with stable performance.
[0034] Comparative Example 1: The difference from Example 3 is that γ-aminopropyltriethoxysilane (KH-550) and sodium dodecyl sulfate (SDS) are removed from the raw materials of the antistatic liquid.
[0035] Comparative Example 2: The difference from Example 3 is that the modified polysaccharide nanoparticles are replaced by a blended particle of 5.5 parts of dialdehyde chitosan, 3.4 parts of konjac glucomannan and 2.1 parts of alginate.
[0036] Experimental example The self-adhesive PET tapes (without release paper) prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for antistatic effect (the resistivity of the antistatic layer of the self-adhesive PET tape was tested by a high insulation resistance meter), and stability in a high-temperature electrolyte environment (the self-adhesive PET tape was immersed in a lithium ion electrolyte at 80° C. for 80 hours, and the viscosity and tensile strength of the self-adhesive PET tape before and after immersion were tested). The results are shown in Table 1.
[0037] Table 1 Performance test results of self-adhesive PET tapes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 The invention forms a stable antistatic system by compounding γ-aminopropyltriethoxysilane (KH-550), dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and sodium dodecyl sulfate (SDS), and forms an antistatic layer on the surface of a PET film base layer by coating. The silanol groups generated by the hydrolysis of KH-550 can undergo a condensation reaction with the hydroxyl groups on the surface of the PET film base layer to form a covalent bond, so that the silane is firmly attached to the surface of the PET film base layer; the dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride can also react with the silanol groups generated by the hydrolysis of KH-550 when a certain hydrolysis reaction occurs, so as to further enhance the adhesion stability of the antistatic system on the surface of the PET film base layer, and SDS is conducive to achieving uniform spreading of the antistatic system on the surface of the PET film base layer.
[0038] The present invention uses polyurethane acrylate, heptadecafluorodecyl triethoxysilane and modified polysaccharide nanoparticles to prepare enhanced self-adhesive glue. The aldehyde group in the dialdehyde chitosan molecule can react with the carboxyl group and hydroxyl group in the alginate molecule and the hydroxyl group in the konjac glucomannan molecule, thereby forming a cross-linked network between the three polymers, which is conducive to the later formation of a film with certain barrier properties, enhances resistance to chemical components, and avoids severe deformation or decomposition at high temperatures. Finally, the enhanced self-adhesive glue is highly stable in a high-temperature electrolyte environment.
[0039] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A self-adhesive PET tape with stable performance, characterized in that: It includes a modified PET film layer, a reinforced self-adhesive glue coated on one side of the modified PET film layer, and an outer layer of removable release paper; The modified PET film layer includes a PET film base layer and an antistatic liquid coated on the surface thereof, wherein the antistatic liquid includes the following raw materials in parts by weight: 5.2 to 7.3 parts of γ-aminopropyltriethoxysilane, 6.6 to 10.4 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, and 1.3 to 2.8 parts of sodium dodecyl sulfate; The enhanced self-adhesive glue comprises the following raw materials in parts by weight: 55-80 parts of polyurethane acrylate, 5-12 parts of heptadecafluorodecyltriethoxysilane and 5-10 parts of modified polysaccharide nanoparticles, wherein the modified polysaccharide nanoparticles are prepared from dialdehyde chitosan, alginate and konjac glucomannan.
2. The self-adhesive PET tape with stable performance according to claim 1, characterized in that: The preparation method of the antistatic liquid comprises the following steps: preparing a mixed solvent according to a volume ratio of ethanol to water = 4:1; slowly dropping γ-aminopropyltriethoxysilane into the mixed solvent under stirring conditions, with a dropping speed of about 1 to 3 drops per second; after the dropping is completed, adjusting the pH value of the solution to 5 to 6, and continuing to stir for 1 to 1.5 hours to fully hydrolyze the γ-aminopropyltriethoxysilane to obtain a hydrolyzate; adding dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and sodium dodecyl sulfate into the hydrolyzate, and continuing to stir for 15 to 25 minutes to obtain the antistatic liquid.
3. The self-adhesive PET tape with stable performance according to claim 1, characterized in that: The preparation method of dialdehyde chitosan is as follows: dissolving chitosan in sodium periodate solution, stirring for 3 hours in a dark place to fully oxidize the chitosan; then adding ethylene glycol solution to terminate the reaction; placing the product in a dialysis bag for dialysis; and finally freeze-drying the dialysate to obtain dialdehyde chitosan.
4. The self-adhesive PET tape with stable performance according to claim 3, characterized in that: Preparation method of the modified polysaccharide nanoparticles: Step (1), preparing a dialdehyde chitosan solution; Step (2), preparing a konjac glucomannan solution; Step (3), adding alginate to the dialdehyde chitosan solution, and magnetically stirring for 15 to 25 minutes to prepare an alginate-dialdehyde chitosan solution precursor; Then, the alginate-dialdehyde chitosan solution precursor was mixed with the konjac glucomannan solution and ultrasonically treated, and then the pH of the solution was adjusted to neutral; Then, the neutral mixture was stirred and incubated at 25-32°C for 1-2 hours at a stirring speed of 350-550 r / min; The nanoparticles are then separated by centrifugation, washed, and dried, and then the modified polysaccharide nanoparticles are frozen at -40 to -70°C for 1 to 3 hours and stored at room temperature.
5. The self-adhesive PET tape with stable performance according to claim 4, characterized in that: In step (1), dialdehyde chitosan is dissolved in 1-1.2% acetic acid solution to obtain a dialdehyde chitosan solution.
6. The self-adhesive PET tape with stable performance according to claim 4, characterized in that: In step (2), konjac glucomannan is dissolved in water having a volume 3 to 5 times that of konjac glucomannan to obtain a konjac glucomannan solution.
7. The self-adhesive PET tape with stable performance according to claim 4, characterized in that: The ultrasonic treatment power is 1200W, and the ultrasonic treatment lasts for 5 to 12 minutes.
8. The self-adhesive PET tape with stable performance according to claim 1, characterized in that: The preparation method of the enhanced self-adhesive glue is as follows: polyurethane acrylate, heptadecafluorodecyl triethoxysilane and modified polysaccharide nanoparticles are mixed at 55-65° C. and then allowed to stand for at least 10 hours to obtain the enhanced self-adhesive glue.
9. A method for preparing a self-adhesive PET tape with stable performance according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Prepare a modified PET film layer. The specific steps are as follows: Step 1.1, prepare antistatic liquid: Prepare a mixed solvent according to the volume ratio of ethanol: water = 4:1; slowly add γ-aminopropyltriethoxysilane to the mixed solvent under stirring, with a drop rate of about 1 to 3 drops per second; after the drop addition is completed, adjust the pH of the solution to 5 to 6, continue stirring for 1 to 1.5 hours, so that the γ-aminopropyltriethoxysilane is fully hydrolyzed to obtain a hydrolyzate; add dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and sodium dodecyl sulfate to the hydrolyzate, continue stirring for 15 to 25 minutes, and obtain an antistatic liquid; Step 1.2, coating the surface of the PET film base with an antistatic liquid, and drying at a low temperature of 55° C. to obtain a modified PET film layer; Step 2: Apply enhanced self-adhesive glue on one side of the modified PET film layer. The specific steps are as follows: Step 2.1, preparing modified polysaccharide nanoparticles: adding alginate to a dialdehyde chitosan solution to prepare an alginate-dialdehyde chitosan solution precursor; Then, the alginate-dialdehyde chitosan solution precursor was mixed with the konjac glucomannan solution and ultrasonically treated, and then the pH of the solution was adjusted to neutral; Then, the neutral mixture was stirred and incubated at 25-32°C for 1-2 hours at a stirring speed of 350-550 r / min; The nanoparticles are then separated by centrifugation, washed, and dried, and then the modified polysaccharide nanoparticles are frozen at -40 to -70°C for 1 to 3 hours and stored at room temperature; Step 2.2, blending polyurethane acrylate, heptadecafluorodecyl triethoxysilane and modified polysaccharide nanoparticles at 55-65° C. and standing for at least 10 hours to obtain an enhanced self-adhesive glue, coating the enhanced self-adhesive glue on one side of the modified PET film layer and drying; Step 3: Paste the removable release paper on the outside of the enhanced self-adhesive glue to obtain a self-adhesive PET tape with stable performance.
10. A self-adhesive PET tape with stable performance prepared according to the method of claim 9.
Citation Information
Patent Citations
Method for preparing functional soluble and edible compound membranes
CN105646951A
Super-wear-resistant and super-amphiphobic coating as well as preparation method and application thereof
CN110240849A
High-viscosity shielding antistatic adhesive tape
CN214528826U
Antistatic hard coat resin composition and antistatic optical article and antistatic resin article
JP2000282014A